Respuesta :

Answer:

s = [tex]\frac{1}{3}[/tex]

Step-by-step explanation:

s = ut + [tex]\frac{1}{2}[/tex] at² ( substitute the given values into the equation )

s = ( 3 × [tex]\frac{1}{3}[/tex] ) + ( [tex]\frac{1}{2}[/tex] × - 12 × ([tex]\frac{1}{3}[/tex] )² )

  = 1 + (- 6 × [tex]\frac{1}{9}[/tex] )

  = 1 + ( - [tex]\frac{2}{3}[/tex] )

  = 1 - [tex]\frac{2}{3}[/tex]

  = [tex]\frac{1}{3}[/tex]

Answer:

[tex] \hookrightarrow \: u = 3 || \: a = - 12 \: || t = \frac{1}{3} \\ \hookrightarrow \: s = ut + \frac{1}{2} a {t}^{2} \\ \hookrightarrow \: s =3 \times \frac{1}{3} + \frac{1}{2} \times - 12 \times (\frac{1}{3} )^{2} \\ \hookrightarrow \: s =1 - \frac{2}{3} \\ \hookrightarrow \: s = \frac{1}{3} [/tex]